Unraveling the genome-wide repertoire of the novel chromosomally encoded mcr-8.6 gene variant in Klebsiella michiganensis isolated from manure - Rivière, Rani; Teixeira, Pedro; Silva, Catarina; Ramos, Miguel; Dias, Elsa; Manageiro, Vera; Caniça, Manuela (Frontiers in Microbiology, 2025)
The increasing rates of colistin resistance worldwide poses a significant threat to public health. While the most commonly described variant is mcr-1, other variants such as mcr-8 have been detected, typically associated with Klebsiella pneumoniae. However, little is known about the prevalence of mcr-8 in other bacterial species and environmental reservoirs. This study aimed to characterize a novel mcr-8 subvariant identified in a Klebsiella michiganensis strain isolated from manure in Portugal, collected during an annual longitudinal survey at an Open Air laboratory, as well as to depict its genomic context and potential mobility mechanisms. The strain was subjected to phenotypic susceptibility testing, whole-genome sequencing and hybrid genome assembly. In silico analysis included identification of resistance genes and mobile genetic element. The new gene variant mcr-8.6 and its genetic environment were characterized. The F731 strain presented susceptibility to colistin with a MIC = 0.25 mg/L, despite carrying a novel mcr-8 subvariant, mcr-8.6, which was located within a 61.6 kb chromosomal genomic island. This variant presented 23–24 amino acid substitutions compared to previous characterized MCR-8 proteins. The genomic island also harbored multiple insertion sequences (IS110, IS66, IS3), virulence factors, and metabolic and regulatory proteins, among others. Synteny analysis revealed high sequence identity between this genomic island and both chromosomal and plasmid regions from other bacterial strains isolated from different reservoirs worldwide, indicating prior mobility. Furthermore, other antimicrobial resistance genes were detected [e.g., aph(3′)-la, blaOXY–1–2], but no plasmid replicons were identified. This is the first report of a mcr-8 gene in a K. michiganensis, as well as the first occurrence in Portugal. Although F731 remains colistin-susceptible, the presence of a novel mcr-8.6 chromosomally encoded but located in a mobile genomic island underscores the risk of future horizontal gene transfer. These findings highlight the importance of further monitoring and continued surveillance in environmental and animal compartments in order to track the dissemination of antimicrobial resistance.